Statistical and text analysis of major accidents to the environment in European Union. Issue 4 (23rd April 2021) - Trávníček, Petr; Tichá, Zuzana; Kotek, Luboš
Abstract: The aim of the paper is to provide operators and authors of safety documents, or responsible authorities, the foundation for decision‐making processes connected with accident risk assessment of major accident to the environment (also on human health or property). Authors worked with hypothesis that there could be some differences between major accidents to the environment and sample of all major accidents. There was performed basic statistical accident data analysis based on public database eMARS. Data was divided into two samples, the first sample included all accidents with environmental impact, the second sample included all accidents mentioned in database. The outputs were compared. The hypothesis was partly confirmed. For example, the pesticides/fertilizer industry category and storage installation type are represented more frequently in major accidents causing immediate damage to the environment (according to Annex VI of European Union's Directive Seveso III). During the database work there were some improvement proposals of the eMARS database in order to improve data processing with efficiency and to provide better access to the information according to the Seveso III directive requirement. These proposals are described in conclusions.